Refugee Crisis And Volunteer Tourism In Lesvos, Greece - Nikolaos Trihas; Konstantinos Tsilimpokos (Journal on Tourism & Sustainability, 2018)
In recent years, Greece has become one of the main gateways for immigrants and refugees seeking safety in Europe. The enormous humanitarian crisis that has taken place mainly on the northeastern Aegean islands has prompted the activation of dozens of organizations and thousands of volunteers. The aim of this study is to examine the profile, motivations and on-site experiences of volunteer tourists who operated on the island of Lesvos in Greece to deal with the refugee crisis. Survey was conducted in a sample of 107 volunteers. The results of the study revealed three altruistic motivations: to help people in need, to do something meaningful and worthwhile, and to work with an organization whose mission they support. Moreover, when choosing a destination to offer their voluntary services, volunteer tourists take into account mainly two factors: the level of need in the destination and the safety in the destination. Volunteers’ perceptions of best experiences were largely linked to the concept of altruism and the social dimension of volunteer tourism, whereas worst experiences highlighted the themes of dead refugees, especially children, and the lack of adequate means to face the massive influx of refugees in the island. Findings and discussion of this study are useful to academic researchers and organizations (NGOs, volunteer organizations, community stakeholders) interested in volunteer tourism.